An integrated scalp and blood biomarker approach suggests the systemic nature of alopecia areata. Issue 10 (17th June 2021) - Glickman, Jacob W.; Dubin, Celina; Dahabreh, Dante; Han, Joseph; Del Duca, Ester; Estrada, Yeriel D.; Zhang, Ning; Kimmel, Grace W.; Singer, Giselle; Krueger, James G.; Pavel, Ana B.; Guttman‐Yassky, Emma
Abstract: Background: Alopecia areata (AA) is characterized by immune dysregulation in both scalp and blood, but a large‐scale approach establishing biomarkers of AA incorporating both scalp tissue and serum compartments is lacking. We aimed to characterize the transcriptomic signature of AA lesional and nonlesional scalp compared to healthy scalp and determine its relationship with the blood proteome in the same individuals, with comparative correlations to clinical AA disease severity. Methods: We evaluated lesional and nonlesional scalp tissues and serum from patients with moderate‐to‐severe AA ( n  = 18) and healthy individuals ( n  = 8). We assessed 33, 118 genes in AA scalp tissue using RNAseq transcriptomic evaluation and 340 inflammatory proteins in serum using OLINK high‐throughput proteomics. Univariate and multivariate approaches were used to correlate disease biomarkers with Severity of Alopecia Tool (SALT). Results: A total of 608 inflammatory genes were differentially expressed in lesional AA scalp (fold change/FCH>1.5, false discovery rate/FDR<0.05) including Th1 (IFNG/IL12B/CXCL11), Th2 (IL13/CCL18), and T‐cell activation‐related (ICOS) products. Th1/Th2‐related markers were significantly correlated with AA clinical severity in lesional/nonlesional tissue, while keratins (KRT35/KRT83/KRT81) were significantly downregulated in lesional compared to healthy scalp ( p  < .05). Expression of cardiovascular/atherosclerosis‐related markers (MMP9/CCL2/IL1RL1/IL33R/ST2/AGER) in lesional scalp correlated with their corresponding serum expression ( p  < .05). AA scalp demonstrated significantly greater biomarker dysregulation compared to blood. An integrated multivariate approach combining scalp and serum biomarkers improved correlations with disease severity/SALT. Conclusion: This study contributes a unique understanding of the phenotype of moderate‐to‐severe AA with an integrated scalp and serum biomarker model suggesting the systemic nature of the disease, advocating for the need for immune‐based systemic treatment. Abstract : Our study contributes a unique understanding of the phenotypic profile of moderate‐to‐severe alopecia areata, suggesting that alopecia areata is a scalp, tissue‐based inflammatory disease, with primarily Th1/Th2/IL‐12/IL‐23 dysregulation. An integrated scalp and serum biomarker model highlights the systemic nature of alopecia areata. Our findings advocate for more targeted therapeutics and emphasize the importance of immune‐based systemic treatments. Abbreviations: CCL, C‐C motif chemokine ligand; CXCL, C‐X‐C motif chemokine ligand; IHC, immunohistochemistry; JAK, Janus kinase; RNAseq, RNA sequencing